Wetting, reactivity, and phase formation at interfaces between Ni–Al melts and TiB2 ultrahigh‐temperature ceramic. Issue 2 (22nd September 2017) - Xi, Lixia; Kaban, Ivan; Nowak, Rafal; Bruzda, Grzegorz; Sobczak, Natalia; Eckert, Jürgen
Abstract: The wetting, reactivity, and phase formation at the liquid Ni–Al/TiB2 ceramic interfaces have been investigated at the temperatures close to the Ni–Al liquidus line. The wetting kinetics has been studied by the sessile drop technique utilizing liquid drop dispension and high‐speed high‐resolution video imaging. It is established that the wetting behavior changes from a nonreactive for the Al‐rich melts to a dissolution‐reactive for the Ni‐rich melts. For the Ni concentration ≥40 at.%, TiB2 precipitates are found in the solidified Ni–Al droplets after the high‐temperature interaction of the melts with TiB2 substrates. Besides, new (Al, Ti)Ni3 and (Al, Ti)2 Ni21 B6 phases are formed due to dissolution of TiB2 ceramic in Ni‐rich melts and subsequent solidification.